2016
DOI: 10.1021/acs.joc.6b01825
|View full text |Cite
|
Sign up to set email alerts
|

Difluoroalkylation/C–H Annulation Cascade Reaction Induced by Visible-Light Photoredox Catalysis

Abstract: We report the first example of difluoroalkylation/C-H annulation cascade reactions of cyclopropyl olefins induced by visible-light photoredox catalysis regioselectively affording partially hydrogenated naphthalenes and quinolines with a variety of difluorinated side chains. The alkylation reagent could be extended to monofluoro and trifluoro reagents, nitrile and malonate. The regioselectivity was investigated by means of density functional theory calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Li's group demonstrated the use of cyclopropyl olens to promote a radical alkylation, ring-opening, intramolecular arylation cascade reaction under photoredox conditions. 26 Fu and co-workers reported that chiral nickel catalysts could achieve enantioselective cross-coupling of a wide range of racemic alkyl halides (as radical precursors) with organometallic nucleophiles 27 including those involving stereoconvergent radical cyclization/arylation. 28 We hypothesize that upon radical formation and in the presence of a pendant vinyl cyclopropane (Scheme 2; right), we could divert reactivity from the crosscoupling cycle to promote an intra-molecular radical cascade reaction.…”
Section: Stereoselective Intra-molecular Dicarbofunctionalization Of mentioning
confidence: 99%
“…Li's group demonstrated the use of cyclopropyl olens to promote a radical alkylation, ring-opening, intramolecular arylation cascade reaction under photoredox conditions. 26 Fu and co-workers reported that chiral nickel catalysts could achieve enantioselective cross-coupling of a wide range of racemic alkyl halides (as radical precursors) with organometallic nucleophiles 27 including those involving stereoconvergent radical cyclization/arylation. 28 We hypothesize that upon radical formation and in the presence of a pendant vinyl cyclopropane (Scheme 2; right), we could divert reactivity from the crosscoupling cycle to promote an intra-molecular radical cascade reaction.…”
Section: Stereoselective Intra-molecular Dicarbofunctionalization Of mentioning
confidence: 99%
“…The cyclopropyl group was quite reactive toward α‐radicals to yield a linear C‐radical after ring‐opening. Using cyclopropyl olefins as radical acceptors, Li has demonstrated a visible‐light‐induced difluoroalkylation/C−H annulation cascade reaction to afford partially hydrogenated naphthalenes and quinolines with diverse difluorinated side chains (Scheme ) . The method was able to accommodate substrates bearing different phenyl rings or pyridines, various α‐bromo compounds functioning as applicable radical donors.…”
Section: Synthesis Of Bicyclic Ringsmentioning
confidence: 99%
“…Quinolines and phenanthridines can also be prepared by cyclization of iminyl radicals obtained by the catalytic photoreduction of O ‐acyl oxime derivatives . The construction of fluorinated heteroarenes (quinolines and isoquinolines) by means of a difluoroalkylation/C–H annulation cascade sequence catalyzed by Ir(ppy) 2 (dtbbpy)PF 6 under blue LED irradiation was also developed . In the same vein, phosphinoyl radical addition onto biphenylyl isonitriles afforded 6‐phosphorylated phenanthridines .…”
Section: Synthesis Of Heteroarenesmentioning
confidence: 99%